A SOLUÇÃO EXTRAJUDICIAL DE CONFLITOS NAS PPP (Reflection and Critique Law Magazine, 2024)
It is the principles of administrative law that allow the judiciary and administration to balance the rights of the administration and the prerogatives of the administration, unifying and systematizing the discipline.  There is still controversy about the possibility of the adoption of alternative means of resolving conflict within the public administration, especially with ballast on the principles of legality and the public interest. In turn, public-private partnerships are contracts through which the public administration agrees for a private sector to provide medium and long-term services. Law No. 11,079/2004 is one of the diplomas that stop the out-of-court settlement of disputes in the country, so it is necessary to analyze this reality in the article.